Tessituras sobre o par docência e corpo na produção acadêmica educacional entre 2018 e 2022 - Paula, Jorge Luiz de (Universidade do Vale do Rio dos Sinos, 2024)
This research presents a critical analysis of the intersection between teaching and the body in educational academic production. The main objective was to investigate the meanings attributed to the pair teaching and the body in academic educational research, specifically in the period between 2018 and 2022. The fields of Teaching Studies, Gender Studies and Body Studies, in conjunction with the poststructuralist perspective, underpin the research and support the analysis. The methodology adopted is meta-research, a systematized critical approach to reviewing existing studies. The results reveal a diversity of approaches to the pair of teaching and the body. On the one hand, the body is often treated in a fragmented way in education, with an emphasis on physical or biological aspects, to the detriment of a more integrated understanding. On the other hand, meanings are identified that associate the body with the construction of identity and the personal and professional development of teachers. The thesis makes it possible to problematize the dichotomies of body and mind, theory and practice, since it identifies and analyses meanings based on an approach that does not distinguish between the concepts of body, teaching and teaching practice in the research examined on teacher training.

Esta pesquisa presenta un análisis crítico de la intersección entre docencia y cuerpo en la producción académica educacional. El principal objetivo fue investigar los sentidos atribuidos al par docencia y cuerpo en las pesquisas educacionales académicas, específicamente en el período entre 2018 y 2022. Los campos de los Estudios en Docencia, de los Estudios de Género y de Cuerpo, en articulación a la perspectiva postestructuralista, basan la pesquisa y sostienen los análisis. La metodología adoptada es la metapesquisa, un abordaje crítico sistematizado de revisión de estudios existentes. Los resultados permiten dar visibilidad a una diversidad de abordajes sobre el par docencia y el cuerpo. Por un lado, el cuerpo es frecuentemente tratado de modo fragmentado en la Educación, con énfasis en los aspectos físicos o biológicos, en detrimento de una comprensión más integrada. Por otro lado, se identifican sentidos que conectan al cuerpo a la construcción de la identidad y al desarrollo personal y profesional de profesores/as. La tesis permite problematizar las dicotomías cuerpo y mente, teoría y práctica, una vez que identifica y analiza sentidos sostenidos en un abordaje que no diferencia los conceptos de cuerpo, docencia y práctica docente en las pesquisas examinadas acerca de la formación de profesores/as.
Keywords: Docência; Corpo; Formação de professores/as; Metapesquisa; Teaching; Body; Teacher training; Meta-research; Docencia; Cuerpo; Formación de profesores/as; ACCNPQ::Ciências Humanas::Educação